The Hidden Diagram. Paper Matter in Origami Practice - Carrubba , Valentina (E|C, 2023)
A destination reserved for paper, origami makes it an incommutable material: only paper can hold so many folds, it’s an irreplaceable element, a kind of principle. This special feature of paper, of generative order (materia mater), more than in the realised artwork, is expressed in the artistic practice, in the relationship between the creative act and the material. Already starting with the origami frame, the Zen spirit animating the art reveals the contrast between a discipline that requires commitment, patience, study, perseverance, and the material it addresses, transient, destined not to last, common and vulnerable (that of paper castles). But if it is true that paper, impermanent, poor, has the effect of thwarting the art’s vocation to the absolute, it is also true that paper has a great memory, and it is in this respect, this ability to keep track, to remember the fold, that origami considers it. Without taking anything away from or adding to the initial extension of the sheet, the architecture of the fold, together with the logic of layering, restores, re-initialises, the structural virtues of the fibre from which the material was originally taken. The paper, which is profiled above all under this temporal-cosmogonic aspect (end, beginning, origin) finds, in the practical scene of origami, with its space and its actors, in the horizon of a strategy and during narrative transformations, a further (inter)definition. From the virtuality of the diagram to the geometric matrix that explains itself on the sheet, from the signed matter that instructs the gesture to the Hyletic component on which the hand adjusts itself and the tool becomes necessary, in the gap between the programme and the execution, this intervention intends to explore the ways in which, through a practice variously attested and first-person experienced, the sense of the material is expressed and managed.